The Influence of Globalization on Distracting Traditional Aesthetic Values in Old Town of Erbil - Zhino Hariry (Journal of Contemporary Urban Affairs, 2017)
Aesthetics as a discipline was originally part of philosophy and cosmology, primarily it was used to create a holistic picture of the world. Throughout history, subject and tasks of aesthetics as a discipline have been changing in different historical, cultural, religious and artistic discourses, nature and the beauty of objects intentionally produced by man, but doubts in the division of aesthetic experiences in comparison to these variants of beauty. One of the cities, where started to rebuild in North Iraq after the Saddam Hussein s regime, was Erbil. This fact has evidently started to come out as a problem of urban conservation that results in the loss of architectural and social values of the historical settings. New building in a historical settlement is an urban conservation problem that forms out a methodology of analyzing and evaluating the existing built fabric with a typological study, making an interpretation of it commenting on the legal regulations and introducing new principles that are based on the synthesis of the past and today for providing historical continuity and preserving urban identity despite the continuous change. The study revealed that by using local and traditional elements in modern architecture there is a possibility to protect the historical building.